2016
DOI: 10.1002/chem.201406655
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Chemical and Toxicological Investigations of a Previously Unknown Poisonous European Mushroom Tricholoma terreum

Abstract: Recent findings casting doubts over the edibility of the European mushroom Tricholoma terreum are questioned on the basis of mycological and mycotoxicological considerations. Accordingly, T. terreum should remain listed among edible mushroom species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Some investigators challenge the findings by Yin et al. () and argue that T. terreum should remain listed among edible mushroom species by indicating that its content of toxic saponaceolides is ambiguously too low to exert any adverse effects on humans even without considering a potential compound loss during mushroom cooking (Davoli, Floriani, Assisi, Kob, & Sitta, ). Additionally, there is no single case of human poisoning linked to T. terreum .…”
Section: Clinical Cases Of Poisoningmentioning
confidence: 99%
“…Some investigators challenge the findings by Yin et al. () and argue that T. terreum should remain listed among edible mushroom species by indicating that its content of toxic saponaceolides is ambiguously too low to exert any adverse effects on humans even without considering a potential compound loss during mushroom cooking (Davoli, Floriani, Assisi, Kob, & Sitta, ). Additionally, there is no single case of human poisoning linked to T. terreum .…”
Section: Clinical Cases Of Poisoningmentioning
confidence: 99%
“…These findings have started an interesting debate among mycologists about the actual toxicity and inedibility of T. terreum [31,32], which is still ongoing. In fact, while the myotoxicity of T. equestre to humans and mice is now well-documented [6], T. terreum is commonly eaten in Europe, mainly in France, Germany, Spain, and Italy [5].…”
Section: Diterpenes: Trichoaurantianolides and Tricholomalidesmentioning
confidence: 99%
“…In fact, while the myotoxicity of T. equestre to humans and mice is now well-documented [6], T. terreum is commonly eaten in Europe, mainly in France, Germany, Spain, and Italy [5]. Moreover, there are no documented cases of poisoning due to the ingestion of T. terreum in Europe and elsewhere, and the medical literature has never reported that consumption of this species induces any symptom related to rhabdomyolysis [31]. Moreover, it has been pointed out that given the amount of saponaceolides B (12) and M (23) contained in the fruiting bodies of T. terreum, toxic levels would need the ingestion of overwhelming amounts of fresh mushrooms.…”
Section: Diterpenes: Trichoaurantianolides and Tricholomalidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In many European countries, this species is considered as dangerous because of the cases of toxic activity, which were reported from 2001 to 2017, with a number of fatalities. Acute poisoning caused by T. equestre, including lethality, was reported from France, Spain, Poland, Lithuania and other countries [5][6][7][8][9].…”
mentioning
confidence: 99%